Error Correction in Teaching Writing Skill:: From Teacher’s Point of View to Practice, A Study at A Pedagogical University in Vietnam - Nguyen Thi Thu Thao; Nguyen Duy Anh (Journal of Development Research, 2017)
In English learning, writing skill is considered, by many people, the most difficult skill to be mas-tered. In fact, errors and mistakes in writing are unavoidable and a large amount of them has been de-tected with a variety of types. Previous researchers have also proved the significance of error analysis and correction in enhancing the writing skills of English learners, but the beliefs and applications of teachers in error correction methods still differ. Thus, the aim of this paper is to investigate these two factors in the teaching and learning environment of a university in Vietnam. The study is conducted in two phases: teacher interview and class observation in practice, with the participation of two Eng-lish teachers who are in charge of teaching writing skill to two classes of 21 and 28 students. The rec-orded results give emphasis to the need of error correction in writing classes, some commonly effec-tive activities utilized; furthermore, there is a remarkable outcome that teachers seldom have academ-ic basis on error correction but mainly depend on their own experience in teaching practice, and their approaching methods to correcting mistakes on students paper can be both direct and indirect. In ad-dition, some ideal activities for error correction, namely peer feedback, on-going writing quizzes, and error codes, are presented